1983
DOI: 10.1042/bj2140489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of certain thiol reagents on alanine transport in plasma membrane vesicles from rat liver and their use in identifying the alanine carrier

Abstract: The Na+-dependent uptake of alanine into plasma membrane vesicles from rat liver was inhibited by N-ethylmaleimide (NEM) and by mersalyl. NEM did not inhibit alanine-independent Na+ uptake and the inhibition of alanine transport by NEM was protected by pre-incubation with an excess of substrate. It was therefore concluded that NEM acted by binding to the alanine carrier. A protein of Mr 20 000 was found to bind NEM with a concentration dependence parallel to the NEM inhibition of alanine transport. The inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
3
9
0
Order By: Relevance
“…Hepatoma cell lines show system A transporters with altered sensitivity to sulfhydryl-modifying reagents [14,29], thus, we wondered whether the activity that develops during liver cell proliferation after partial hepatectomy could have any similarity with the one present in hepatoma cells. Sensitivity of system A to agents like NEM results in irreversible inactivation, which can be protected by the presence of system A substrate [14,29,30], thus supporting the idea that -SH groups are essential for substrate recognition and translocation. Altered sensitivity to NEM was consistent with carriers structurally different in hepatoma cells.…”
Section: Nem (Mm1mentioning
confidence: 68%
“…Hepatoma cell lines show system A transporters with altered sensitivity to sulfhydryl-modifying reagents [14,29], thus, we wondered whether the activity that develops during liver cell proliferation after partial hepatectomy could have any similarity with the one present in hepatoma cells. Sensitivity of system A to agents like NEM results in irreversible inactivation, which can be protected by the presence of system A substrate [14,29,30], thus supporting the idea that -SH groups are essential for substrate recognition and translocation. Altered sensitivity to NEM was consistent with carriers structurally different in hepatoma cells.…”
Section: Nem (Mm1mentioning
confidence: 68%
“…Inhibition of system A and ASC transport activities by NEM It has previously been reported that NEM inhibits alanine uptake by plasma-membrane vesicles from rat liver (Sips & Van Dam, 1981;Hayes & McGivan, 1983). It has also been reported that the thiol-modifying reagent p-chloromercuribenzenesulphonate has a direct effect on a-aminoisobutyric acid (AIB) transport in several hepatoma cell lines (Dudeck et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of high concentrations of substrates (10 mM-L-alanine+ 100 mM-NaCI), the inhibition of Na+-dependent alanine uptake induced by 10 min of exposure to 30 mM-IA was substantially slowed down (Table 5). Under these conditions, the presence of substrates during the exposure of membranes to IA partially protected system A and ASC transport activities ( previous observations regarding the protective effect of L-alanine on NEM-dependent blocking of alanine transport in rat liver plasma membranes (Hayes & McGivan, 1983). In addition, a direct effect of p-chloromercuribenzene sulphonate, another sulphydryl-modifying reagent, has been reported on AIB transport (A + ASC) in membrane vesicles from H4 hepatoma cells (Dudeck et al, 1987).…”
Section: Na+-dependentmentioning
confidence: 99%
See 2 more Smart Citations